Primary rectal monophasic synovial sarcoma. Issue 4 (4th July 2021) - Zhang, Junlin; Findeis, Sarah K.; Lang, Benjamin J.; Ogola, Gerald O.; Agarwal, Atin
Abstract: Synovial sarcoma is a rare malignant mesenchymal neoplasm that often occurs in the extremities. Less than 70 cases of primary synovial sarcoma occurring in the digestive system have been reported. We present a case of a 48-year-old woman with a spindle cell tumor in the rectum that stained positive for AE1/3 (focal), vimentin, CD99, BCL2, EMA (focal), and MiB-1 (15%). Ultimately, the lesion was diagnosed as a primary rectal monophasic synovial sarcoma and confirmed by molecular testing for SYT/SSX1 gene fusion. Analysis of previous publications indicated that patients of advanced age or a large tumor size (≥5 cm) have a higher risk of progressing rapidly to death after diagnosis of synovial sarcoma in the digestive system.